EFL Students’ Perception on Translation Effects Toward Their L1 and L2 Empowerment: Reestablishing the Use of Translation in FL Teaching - Sudarya Permana (Stairs, 2020)
This paper aims to discuss EFL students’ perception on translation effects toward their L1 and L2 empowerment. The data were taken from fifty-two students who had passed the course of translation, both L1 to L2 and L2 to L1. To gain the data, a researcher-developed questionnaire was distributed to find out students’ perception, consisting of a closed-ended and an open-ended questionnaire. From the statistical findings, it was revealed that in terms of the four main language skills, namely reading, listening, speaking, and writing, students perceived that translation was able to empower their L1 and L2 reading, listening, and writing, but with little contribution to their L1 and L2 speaking. In addition to these three language skills, the translation course was also able to empower students in the L1 and L2 grammar and vocabulary mastery.